Peran Majelis Kehormatan Notaris terhadap Pejabat Notaris yang Menggunakan Hak Ingkar dalam Menjaga Kerahasiaan Isi Akta - Aditya Laras Sakti Sudarsono; Achmad Faishal (AHKAM, 2026)
Although the notary’s right of refusal and the protection of deed confidentiality have received attention in various previous studies, studies that specifically discuss the role of the Notary Honorary Council in providing protection for notaries who exercise the right of refusal, as well as the limits of its use in legal examination processes, remain limited. This study aims to analyze the factors considered by the Notary Honorary Council in accepting or rejecting requests for approval to examine notaries by investigators, public prosecutors, or judges, as well as to analyze the existence and limits of the use of the notary’s right of refusal in legal examination processes. This study used a qualitative approach with a normative legal research design through a statutory approach and a conceptual approach. Primary, secondary, and tertiary legal materials were obtained through literature study and were then analyzed descriptively-prescriptively by examining relevant laws and regulations, legal doctrines, and literature. The results showed that the Notary Honorary Council has a strategic role in providing legal protection for notaries through its authority to approve or reject requests for the summoning of notaries and the retrieval of notarial protocol documents by law enforcement officials. In exercising this authority, the Notary Honorary Council considers the urgency of the examination, the relevance of the deed to the case being examined, and the need for evidence in the judicial process. The results also showed that the notary’s right of refusal remains recognized as a consequence of the obligation to maintain the confidentiality of the office and the contents of deeds, but its use is not absolute because it is limited by statutory provisions and the interests of law enforcement through established mechanisms. This finding contributes to the development of notarial law studies, particularly regarding the relationship between the protection of notarial office confidentiality and the need for law enforcement in judicial proceedings. The conclusion of this study emphasizes that the use of the right of refusal must be applied proportionally by maintaining a balance between the protection of notarial office confidentiality and the interest of seeking truth in legal proceedings. The implications of this study include theoretical contributions to the development of the concept of legal protection for the notarial profession, as well as practical implications for the Notary Honorary Council, law enforcement officials, and policymakers in creating a notarial examination mechanism that ensures legal certainty and balanced professional protection.